Operations on covering numbers of certain graph classes - Chandoor, Susanth; Kalayathankal, Sunny Joseph (International Journal of Advanced Mathematical Sciences, 2016)
The bounds on the sum and product of chromatic numbers of a graph and its complement are known as Nordhaus-Gaddum inequalities. In a similar way, the operations on the covering numbers of graphs with their complement are studied and with respect to this, new characterizations of certain graph classes have also been given in this paper.